Maternal and Breast Milk Influences on the Infant Gut Microbiome, Enteric Health and Growth Outcomes of Rhesus Monkeys. Issue 3 (September 2019) - Rendina, Danielle Nicole; Lubach, Gabriele R.; Phillips, Gregory J.; Lyte, Mark; Coe, Christopher L.
ABSTRACT: Objectives: Gut bacteria play an essential role during infancy and are strongly influenced by the mode of birth and feeding. A primate model was used to investigate the benefits of exposure to the mother or conversely the negative impact of early nursery rearing on microbial colonization. Method: Rectal swabs were obtained from rhesus macaques born vaginally and mother-reared (MR, N = 35) or delivered primarily via cesarean-section and human-reared (HR, N = 19). Microbiome composition was determined by rRNA gene amplicon sequencing at 2, 4, and 8 weeks of age and Kyoto Encyclopedia of Genes and Genomes (KEGG) orthologs used to assess influences on functional metabolic pathways in the gut. Growth trajectories and incidence of diarrheic symptoms were evaluated. Results: The microbial community structure was different between MR and HR infants with respect to phylogeny and abundance at all 3 ages. When examining dominant phyla, HR infants had a higher Firmicutes-to-Bacteroidetes ratio. At the genus level, breast milk-dependent commensal taxa and adult-typical genera were more abundant in MR infants. This difference resulted in a corresponding shift in the predicted metabolic effects, specifically for microbial genes associated with metabolism and immune function. HR infants had faster growth trajectories ( P  < 0.001), but more diarrheic symptoms by 6 months postnatal ( P  = 0.008). Conclusions: MR infants acquired adult-typical microbiota more quickly, and had higher levels of several beneficial commensal taxa. Cesarean-delivered and formula-fed infants had different developmental trajectories of bacterial colonization. Establishment of the gut microbiome was associated with an infant's growth trajectory, and implicated in the subsequent vulnerability to Campylobacter infections associated with diarrhea in infant monkeys. Abstract : Supplemental Digital Content is available in the text